1982
DOI: 10.1210/jcem-54-1-182
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Adrenocorticotropin Deficiency Associated with Polyglandular Failure

Abstract: A female patient presented with isolated ACTH deficiency and diabetes mellitus. During the course of a year's replacement with hydrocortisone, goiter developed, which, on biopsy, was diagnosed as typical Hashimoto's thyroiditis. Four years later, she experienced tetany, and the diagnosis of idiopathic hypoparathyroidism was made. Immunological studies revealed the presence of antithyroid antibodies in the serum and cell-mediated immunity to the thyroid and parathyroid. These data strongly suggest that the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…all, forms of IAD [2][3][4]. These findings strongly suggest the involvement of autoimmune processes in the pathogenesis of IAD.…”
mentioning
confidence: 58%
“…all, forms of IAD [2][3][4]. These findings strongly suggest the involvement of autoimmune processes in the pathogenesis of IAD.…”
mentioning
confidence: 58%
“…It has been suggested that some autoimmune disorders are at least partly involved in isolated ACTH deficiency and pregnancy-related hypophysitis [4][5][6]. PGA syndromes associated with isolated pituitary hormone (ACTH, GH or gonadotropin) secretion failure have been reported [7][8][9]. Here we report two patients with isolated ACTH deficiency, one patient with isolated TSH deficiency and one patient with gonadotropin deficiency associated with other autoimmune endocrine disorders.…”
Section: The Coexistencementioning
confidence: 79%
“…The endocrinological features seen at the end of this study were compatible with LAH, decreased response of TSH, GH and FSH and increased response of prolactin to the respective stimulating hypothalamic hormones. Several reports have suggested that LAH might have caused acquired isolated deficiency of pituitary hormones [1,[18][19][20][21][22]. Actually, several types of isolated pituitary hormone deficiency associated with LAH have been reported [13,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%